Token ekonomi dengan media flashcard untuk meningkatkan kemampuan membaca permulaan pada anak disleksia - Susanti Prasetyaningrum; Sri Yunita Mauliza; Ahmad Sulaiman (Cognicia, 2022)
Dyslexia is a specific form of learning disorder related to difficulty reading and difficulty in writing expression. Most dyslexia children show low ability in overall phonological processing, leading to slower reading development than other children. Therefore, intervention methods are needed that are tailored to the characteristics of dyslexic children, one of which is a flashcard medium with the principle of economic tokens. The purpose of this study was to find out the effectiveness of flashcard media with the principle of economic token to the ability to read early in dyslexic children. The study uses a quantitative approach of single-case experimental design. The subjects in the study were a second grader aged 7 years and exhibited dyslexia characteristics as well as experiencing barriers in initial reading. Then the instrument used to measure the ability to early level reading ability EGRA (Early Grade Reading Assessment). The results of this study show that flashcard media with the principle of economic tokens is effective for improving the early level reading ability in dyslexia children. Keywords: Dyslexia, early level reading ability, flashcard, token economy